Gouvernance territoriale et perception du risque à la suite de l’inondation de la rivière Richelieu en 2011 - Daniel Germain; Jonathan Pelletier; Catherine Trudelle; Marilyne Gaudette (VertigO, 2022)
Coordination and cooperation between public and private actors and the population, as well as the articulation of different geographical scales in the elaboration of territorial strategies, have become essential elements in the prevention of natural risks. From this perspective, it is appropriate to look at the territorial governance of the Quebec system, in particular whether risk management still depends on a traditional system in which citizens have very little decision-making power. In this regard, the level of citizen accountability was studied in the municipality of Saint-Jean-sur-Richelieu to understand the role of stakeholders in the management of the flood that occurred in the spring of 2011. Questionnaires were distributed to the population in two flood-prone neighborhoods to observe the prevention and preparedness practices of riverside residents regarding spring flooding, and semi-directed interviews were conducted with several key stakeholders in risk management. The results showed that an update of knowledge was essential because of climate change and that there is a considerable gap in the establishment of the functions and skills of all the stakeholders. Moreover, this lack of a clear definition of the role of individuals leads to a disempowerment and negation of risks, particularly at the municipal level. Finally, while our analysis shows a significant gap in territorial governance in risk management in Quebec, it must be noted that some partnerships and the new policies put in place since nevertheless contribute to increasing the resilience of Quebec society.